Joint construction of micro-vibration stimulation and BCP scaffolds for enhanced bioactivity and self-adaptability tissue engineered bone grafts. Issue 19 (20th April 2020) - Wu, Jinjie; Chen, Taijun; Wang, Zhenxiong; Chen, Xuening; Qu, Shuxin; Weng, Jie; Zhi, Wei; Wang, Jianxin
Abstract : The bone defects caused by trauma and disease have become a major difficulty in the treatment of clinical bone defects, and bone tissue engineering has become a promising treatment strategy. Abstract : The bone defects caused by trauma and disease have become a major difficulty in the treatment of clinical bone defects, and bone tissue engineering has become a promising treatment strategy. It was found that mechanical stimulation regulated the development of bone constructs by affecting the distribution and differentiation of cells on them. In this study, tissue-engineered bone grafts with enhanced bioactivity and self-adaptability were constructed by BMSCs and biphasic calcium phosphate (BCP) scaffolds under periodic micro-vibration stimulation (MVS) with a frequency of 40 Hz and a magnitude of 0.3 g. The results of the material characterization indicated that the BCP scaffolds created a more favourable osteogenic micro-environment with promoted calcium ion release, protein adsorption and mineralization deposition under the micro-vibration stimulation. The in vitro results showed that the apoptosis of BMSCs increased significantly on day 1, but from day 3 on, the proliferation increased and apoptosis decreased. Cells were evenly distributed on the scaffolds, exhibiting tight adhesion in a flat-shape and distinct matrix mineralization. F-actin and ALP expression significantly increased and meanwhile osteogenesis-related genes including Runx2, Col-I, ALP, and OCN were significantly up-regulated. Western blotting results suggested that the ERK1/2 and Wnt/β-catenin signalling pathways were involved in the osteogenic behaviour of BMSCs induced by MVS. In vivo experiments showed that grafts had stronger osteoinduction and mechanical adaptability. Taken together, this study suggested that micro-vibration stimulation combined with BCP scaffolds with good osteoinduction could be a promising approach for constructing tissue engineered bone grafts with enhanced bioactivity, mechanical adaptability, and bone regeneration repair capability.